QUALITY MANAGEMENT IN THE AGRICULTURAL ENVIRONMENT: A CASE STUDY OF THE APPLICATION OF ROUTINE MANAGEMENT IN THE SUCROENERGETIC SECTOR - Martins, G. A.; Baesso, M. M. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The sugarcane industry is looking for higher yields that justify the production of sugar, ethanol and bioenergy for theirs investors. Agricultural maintenance needs to deliver a high level of quality in its service to ensure that the equipment works at its maximum availability to achieve such productivity. The use of new management methods, are ways to seek such results, such as quality management. The case study was developed from the application of quality management tools in the area of agricultural maintenance in a -mill in the sucroenergetic sector. Between pre and post periods of routine management application an increase of 22,79 ton.mach-1.day-1 in the productivity of sugar cane harvester was observed. The results showed that although it needs more time to express a greater potential for process improvement, the routine management methodology has brought benefits to the agricultural maintenance area.